13.9k views
1 vote
Expand each expression::


log_(9) (6x^(3) y^(5) z^(2))


In(\frac{x^(7) }{\sqrt{&y-1)z^(3) } } )


In(\frac{\sqrt[3]{ab^(2) } }{\sqrt{yz^(5) } } )

1 Answer

2 votes

Answer:


log_(9)6+3log_(9)x+5log_(9)y+2log_(9)z


7lnx-(1)/(2)ln(y-1)-(3)/(2)lnz


(1)/(3)lna+(2)/(3)lnb-(1)/(2)lny-(5)/(2)lnz

Explanation:


log_(9)(6x^(3)y^(5)z^(2))=


log_(9)6+log_9}x^(3)+log_(9)y^(5)+log_(9)z^(2)=


log_(9)6+3log_(9)x+5log_(9)y+2log_(9)z


ln\frac{x^(7)}{\sqrt{(y-1)z^(3)}}=lnx^(7)-ln[(y-1)z^(3)]^{(1)/(2)} =


7lnx-ln(y-1)^{(1)/(2)}(z^(3))^{(1)/(2)}}=


7lnx-ln(y-1)^{(1)/(2)}-lnz^{(3)/(2)}=


7lnx-(1)/(2)ln(y-1)-(3)/(2)lnz


ln\frac{\sqrt[3]{ab^(2)}}{\sqrt{yz^(5)}}=


ln(ab^(2))^{(1)/(3)}-ln(yz^(5))^{(1)/(2)}=


ln(a)^{(1)/(3)}(b)^{(2)/(3)}-ln(y)^{(1)/(2)}(z)^{(5)/(2)}=


(1)/(3)lna+(2)/(3)lnb-(1)/(2)lny-(5)/(2)lnz

User Germi
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.